2012
DOI: 10.2174/138161212802430549
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Study of the Oligosaccharide Binding Sites in the Lectin-Like Domain of Tumor Necrosis Factor and the TNF-derived TIP Peptide

Abstract: The lectin-like domain of Tumor Necrosis Factor (TNF), mimicked by the TIP peptide, activates amiloride-sensitive sodium uptake in type II alveolar epithelial cells and as such increases alveolar liquid clearance in dysfunctional lungs. This protective effect is blunted upon mutation of residues T105, E107 and E110 in human TNF into alanine or upon pre-incubation of the cytokine with the disaccharide N,N’-diacetylchitobiose. In this study, we used molecular docking and molecular dynamics simulation to predict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
3
5
0
Order By: Relevance
“…These results correspond to data from a study of molecular docking between TNF and N,N9-diacetylchitobiose, indicating that oligosaccharide binding to TNF sterically hinders its association with residues involved in the Na 1 uptake stimulating effect of the cytokine (40).…”
Section: As Shown Insupporting
confidence: 86%
See 1 more Smart Citation
“…These results correspond to data from a study of molecular docking between TNF and N,N9-diacetylchitobiose, indicating that oligosaccharide binding to TNF sterically hinders its association with residues involved in the Na 1 uptake stimulating effect of the cytokine (40).…”
Section: As Shown Insupporting
confidence: 86%
“…The puzzling observation that oligosaccharides can blunt the binding of the TIP peptide to recombinant, and thus nonglycosylated, subunits can be explained by our previously published molecular docking study indicating that residues involved in the binding of human TNF to N,N9-diacetylchitobiose are different from, but spatially close to, those necessary for activation of Na 1 uptake (40). Indeed, the mutant TIP peptide, which has a strongly reduced capacity to bind to ENaC-a and activate ENaC, still efficiently binds to N,N9-diacetylchitobiose (59).…”
Section: Discussionmentioning
confidence: 99%
“…This was demonstrated in whole-cell recordings and in singlechannel experiments in both endogenously as well as heterologously expressed hENaC. Recent docking and molecular dynamics simulation experiments indicated that the TIP peptide AP301 represents a partial binding motif for chitobiose (Dulebo et al, 2012). By definition, lectins bind to glycans, and our data clearly show that glycosylation of ENaC is necessary for activation with AP301.…”
Section: Ap301-induced Activation Of Henacsupporting
confidence: 70%
“…Deglycosylation with -(N-Acetyl-b-D-Glucosaminyl)Asparagine Amidase F. Docking and molecular dynamics simulation experiments indicated that the TIP peptide AP301 represents a partial binding motif for chitobiose (Dulebo et al, 2012). To investigate a possible interaction of TIP peptides with sugar moieties on the cell membrane, deglycosylation of A549 as well as transfected and nontransfected HEK-293 cell membranes was performed with peptide-N 4 -(N-acetyl-b-D-glucosaminyl)asparagine amidase F (PNGase F, peptide N-glycanase) at room temperature.…”
Section: Electrophysiologymentioning
confidence: 99%
“…All energy calculations and minimizations/dynamics used periodic boundary conditions and the YAMBER3 force field34. The system was then energy-minimized using steepest descent minimization, in order to remove conformational stress, followed by a simulated annealing minimization until convergence (<0.05 kJ per mol per 200 steps).…”
Section: Methodsmentioning
confidence: 99%